2020
DOI: 10.1515/pac-2019-0809
|View full text |Cite
|
Sign up to set email alerts
|

Interlaboratory comparison of humic substances compositional space as measured by Fourier transform ion cyclotron resonance mass spectrometry (IUPAC Technical Report)

Abstract: Interlaboratory comparison on the determination of the molecular composition of humic substances (HS) was undertaken in the framework of IUPAC project 2016-015-2-600. The analysis was conducted using high resolution mass spectrometry, nominally, Fourier transform ion cyclotron resonance mass spectrometry (FTICR MS) with electrospray ionization. Six samples of HS from freshwater, soil, and leonardite were used for this study, including one sample of humic acids (HA) from coal (leonardite), two samples of soil H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Relative abundance weighted metrics of the mass, AI mod , NOSC, heteroatomic content (i.e., CHO, CHON, CHOS, CHONS), and formulae categories are reported in Table 1. In this study, we focus on changes in these metrics and relative abundance in formula categories, as this has shown to be most robust for comparisons across instruments (Hawkes et al., 2020; Zherebker et al., 2020). Suwanee River Fulvic Acid Standard (2S101F) showed < 2% difference in relative abundance of formula categories across instruments.…”
Section: Methodsmentioning
confidence: 99%
“…Relative abundance weighted metrics of the mass, AI mod , NOSC, heteroatomic content (i.e., CHO, CHON, CHOS, CHONS), and formulae categories are reported in Table 1. In this study, we focus on changes in these metrics and relative abundance in formula categories, as this has shown to be most robust for comparisons across instruments (Hawkes et al., 2020; Zherebker et al., 2020). Suwanee River Fulvic Acid Standard (2S101F) showed < 2% difference in relative abundance of formula categories across instruments.…”
Section: Methodsmentioning
confidence: 99%
“…34,36,43,44 It is worth noting that the number of assigned molecular formulae may be dependent on the sampling method, SPE procedure, ionization mechanism, FT-ICR MS parameters, and data acquisitions, but recent studies have shown robust comparisons across instruments regarding the parameters examined here. 45,46 FT-ICR MS results in our study show that the initial cryoconite DOM solution (d 0 ) is enriched with CHO (containing 3−16 oxygen) (40%) and CHON (containing 1−3 nitrogen and 3−13 oxygen) (49%) elemental formulae, followed by CHOS (containing 1 sulfur and 5−9 oxygen) (7.7%) and CHONS (containing 1 sulfur, 1 nitrogen, and 5−8 oxygen) (3.3%) (Table S1). Classification of the molecular formulae in the d 0 sample by the defined categories in the methods suggested that the majority of the identified formulae correspond to aliphatic (25.9%) and peptide-like (20.1%) assignments, which is highly comparable to data from Himalayan snowpack/ice samples (23.9 and 20.4% aliphatic and peptide-like, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, FTICR-MS made it possible to assign more than 6500 unique gross formulas in the study of compounds of humic origin [ 171 ]. Comparative studies have shown that the absence of a generally accepted protocol for such studies significantly affects the interlaboratory reproducibility of results [ 172 ].…”
Section: Omics Sciences In Inanimate Naturementioning
confidence: 99%